(untitled) (Al-Qamar, 2023)
This article studies the reflections of feminine society in Masnavis of Momin Khan Momin. It finds that Momin khan Momin was the important Manavi writer of his time. He was poet of love & beauty. Momin refreshed/revolutionized/recreated feminine culture of India with his Masnavies. Momin wrote total 12 Masnavies, 6 of them was about love. In these 6 Masnavies we observe the awareness, the feeling of feminine culture. In his Masnavies, Momin used feminine character to create attractive & interesting dialogues. In his every Masnavi, we see rival adversary competitor woman in her society.